Activation of the intestinal tissue renin-angiotensin system by transient sodium loading in salt-sensitive rats. Issue 1 (19th January 2022) - Ryuzaki, Masaki; Miyashita, Kazutoshi; Sato, Masaaki; Inoue, Hiroyuki; Fujii, Kentaro; Hagiwara, Aika; Uto, Asuka; Endo, Sho; Oshida, Takuma; Kinouchi, Kenichiro; Itoh, Hiroshi
Abstract : Supplemental Digital Content is available in the text Abstract : Background: The renal tissue renin-angiotensin system is known to be activated by salt loading in salt-sensitive rats; however, the response in other organs remains unclear. Method: Spontaneously hypertensive rats were subjected to normal tap water or transient high-salt-concentration water from 6 to 14 weeks of age and were thereafter given normal tap water. From 18 to 20 weeks of age, rats given water with a high salt concentration were treated with an angiotensin II type 1 receptor blocker, valsartan. Results: Sustained blood pressure elevation by transient salt loading coincided with a persistent decrease in the fecal sodium content and sustained excess of the circulating volume in spontaneously hypertensive rats. Administration of valsartan sustainably reduced the blood pressure and normalized the fecal sodium levels. Notably, transient salt loading persistently induced the intestinal tissue renin-angiotensin system and enhanced sodium transporter expression exclusively in the small intestine of salt-sensitive rats, suggesting the potential connection of intestinal sodium absorption to salt sensitivity. Conclusion: These results reveal the previously unappreciated contribution of the intestinal tissue renin-angiotensin system to sodium homeostasis and blood pressure regulation in the pathophysiology of salt-sensitive hypertension.